2015
DOI: 10.1128/jvi.03437-14
|View full text |Cite
|
Sign up to set email alerts
|

Analysis by Live Imaging of Effects of the Adenovirus E4orf4 Protein on Passage through Mitosis of H1299 Tumor Cells

Abstract: The adenovirus E4orf4 protein expressed at high levels kills cancer cells but not normal human primary cells. Previous studies suggested that disruption of processes that regulate mitosis may underlie E4orf4 toxicity. Here we have used live imaging to show that E4orf4 induces a slowed defective transit through mitosis, exhibiting a delay or often failure in cytokinesis that may account for an accumulation of G 1 tetraploids in the population of dying E4orf4-expressing cells. E4orf4 is a human adenovirus early … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…The degree of recruitment could be cell cycle dependent (64). The finding that PARP inhibition did not completely abolish E4orf4-induced cell death may result from the fact that E4orf4 interferes with additional cellular pathways, such as cell cycle regulation (36,65), and their disruption can contribute to cancer cell death in a PARP-independent manner. It is also possible that the activity of the PARP inhibitor diminished with time during the 24-h incubation with the cells even though a second aliquot was added after 12 h.…”
Section: Discussionmentioning
confidence: 99%
“…The degree of recruitment could be cell cycle dependent (64). The finding that PARP inhibition did not completely abolish E4orf4-induced cell death may result from the fact that E4orf4 interferes with additional cellular pathways, such as cell cycle regulation (36,65), and their disruption can contribute to cancer cell death in a PARP-independent manner. It is also possible that the activity of the PARP inhibitor diminished with time during the 24-h incubation with the cells even though a second aliquot was added after 12 h.…”
Section: Discussionmentioning
confidence: 99%
“…It was suggested that these cells were in the G1 phase of the cell cycle rather than in G2/M and that they progressed from mitosis to G1 in the absence of cytokinesis [ 54 ]. These results were further confirmed by time-lapse microscopy experiments demonstrating that E4orf4 slowed down dramatically the transit of H1299 cells through mitosis and caused a delay or failure of cytokinesis [ 55 ]. E4orf4-induced perturbation of cytokinesis was also observed in yeast cells, which displayed abnormal budding [ 17 , 18 , 45 ] ( Figure 2 ).…”
Section: The Unique Mode Of E4orf4-induced Cell Deathmentioning
confidence: 72%
“…Defects in cytokinesis were also observed in E4orf4-expressing yeast cells which manifested abnormal budding [18,21,68]. Live imaging of E4orf4-expressing H1299 cells confirmed that E4orf4 slowed down the transition of cells through mitosis and disrupted cytokinesis [69]. E4orf4-expressing cells were also defective in initiation of DNA replication [67].…”
Section: Effects Of E4orf4 On the Cell Cyclementioning
confidence: 99%